Design and application of a special auricular acupoint treatment tool bag (一种特制耳穴治疗工具袋的设计与应用) - ZHAO Lingling (赵玲玲); XIE Wei (谢薇); HE Yanlin (何燕琳); XIANG Yiming (向毅明); LUO Liyuan (罗丽媛); ZHOU Yihan (周艺涵) (Association of Integrative Nursing, 2023)
This article introduced a special auricular acupoint treatment tool bag. The tool bag is designed for effectively utilizing the space and placing various tools for auricular acupoint treatment. The special auricular acupoint treatment tool bag not only meets the operation needs, but also saves time and improves work efficiency, which is worthy of clinical application. (本文介绍了一种特制耳穴治疗工具袋的设计与应用, 该工具袋充分利用空间, 可分别放置耳穴治疗所需各种工具, 且方便取用, 节约了时间成本, 提高了工作效率。)